A Simplified Design for a Split-Hopkinson Tension Bar with Long Pulse Duration. (2017) - Ganzenmüller, G.C.; Blaum, E.; Mohrmann, D.; Langhof, T.; Plappert, D.; Ledford, N.; Paul, H.; Hiermaier, S.
Abstract: This paper presents a simplified design for a Split-Hopkinson Tension Bar (SHTB) which allows for pulse durations exceeding one millisecond. This testing apparatus is intended for material characterization requiring large amounts of elongation, necessitated either by large specimen dimensions, or large strains to failure. The design proposed here can be assembled from off the shelve components without the need for specialized machining tools. The simple mechanical design is accompanied by a comparatively low-cost, yet high-speed, means of independently measuring specimen strain using a fast line scan camera. The performance of this SHTB implementation is demonstrated by obtaining intermediate strain rate results for tensile yield strength of Polycarbonate in an unprecedented quality.